Writing the private eye novel : a handbook - Randisi, Robert J. (Writer's Digest Books, 1997)
Writing the Private Eye Novel is a vaulable resource for anyone who wants to try to make a living writing detective fiction. Obviously, there is no formula that guarantees success, but in this collection of essays from working authors, you can get a very good idea of what you should be thinking about and where to direct your creative energy.